Ergonomic risk analysis for drone pilots - Elizalde, Rubén Rodríguez (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyse the ergonomic risks faced by drone pilots, focusing on postural chal-lenges during flight operations. The research investigates how these postures may contribute to musculoskeletal disorders and proposes corrective measures to mitigate these risks. The study utilized the Rapid Upper Limb Assessment (RULA) methodology to evaluate the postures adopted by drone pilots during real flight operations. Observations were conducted across multiple work cycles involving two drone pilots operating in different environments. Angular measurements of various body segments were captured and analysed to determine ergonomic risk levels. The analysis identified five key postures that posed varying levels of ergonomic risk. Three postures were found to require possible adjustments, while two required task redesign due to significant musculoskeletal strain. Key risk factors included prolonged wrist extension, neck flexion, and static load caused by the control console's design and the pilot’s need to maintain visual contact with the drone. The study concludes that ergonomic risks for drone pilots are significant and require proactive interventions. Recommendations include adopting improved console designs, incor-porating harness support systems, modifying operational protocols to improve body positioning, and utilizing alternative equipment like larger display screens to reduce neck strain. The findings offer actionable insights for drone operators, ergonomics specialists, and employers to implement ergonomic improvements in drone piloting tasks. These changes aim to reduce musculoskeletal disorders, improve working conditions, and enhance overall safety in drone operations.